Heart lesions in children affected by COVID-19 - Yu. B. Belan; E. A. Gashina; E. F. Lobova; T. E. Shvets (Детские инфекции (Москва))
Ongoing research on SARS-CoV-2 showed the ability of a pathogen to affect cardio-vascular system in the form of myocarditis, dysrhythmia, cardiac failure, etc. According to an infectious diseases hospital in Omsk, changes in the heart were recorded in 3.3% of children hospitalized with COVID-19. Authors conducted a retrospective study of 24 children aged 1—17 years 11 months with a new coronavirus infection who recieved treatment in an infectious diseases hospital at the Budgetary Healthcare Institution of Omsk Oblast City Children's Clinical Hospital №3 in Omsk from October 2020 to December 2021. It was found that heart lesions were more often recorded in children over 10 years old, all males. In most patients, cardiac lesions developed in presence of concomitant pathology and were combined with lung damage. Clinical manifestations indicating involvement in the pathological process of the cardiovascular system appeared in addition to respiratory infection. They were mild and nonspecific.